JOB SATISFACTION: DISCIPLINE, QUALITY, AND ORGANIZATIONAL CULTURE AMONG ALFAMART AND INDOMARET EMPLOYEES IN BANDUNG CITY - Lailatun Mubarokah; Deddy Fardillah (Jurnal Manajemen Sains dan Organisasi, 2024)
Objective – This study aims to examine the influence of work discipline, work quality, and organizational culture on employee job satisfaction.Design/Methodology/Approach – The research employs a quantitative approach with a sample size of 100 employees. To empirically test the relationships between the proposed variables, the study uses the Multiple Linear Regression method with SPSS software.Findings – The results indicate that work discipline, work quality, and organizational culture have a positive and significant impact on employee job satisfaction at Alfamart and Indomaret in Bandung City.Conclusion and Implications – Increased staff discipline is associated with higher levels of job satisfaction, indicating that work discipline significantly affects job satisfaction. Workers who consistently put in high-quality effort tend to be happier as cashiers and other retail business associates. Keywords: Work Discipline, Work Quality, Organizational Culture, Job Satisfaction